Ornamenty Usekskoi doliny . Ornamenty Usekskoi doliny . Ornamental Pattern of Usekskoi Valley . Орнаменты Усекской долины - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
This program was broadcast by the state television (Moscow) in the USSR and recorded by the Radio Liberty Monitoring Unit in Munich as part of their effort to track and analyze the official media of the republics of the Soviet Union. Передача государственного телевидения (Москва, СССР) была записана отделом мониторинга радиостанции Свобода (Мюнхен) как часть проекта по анализу официальных средств информации республик Советского Союза. The documentary discusses folk ornaments, which reflect thoughts and emotions of their makers. Contributors: IAkshimbetov, Malik (Director); Rudnev, A. (Camera); Karabalin, A. (Camera); Kazakhtelefil'm (Studio) Фильм о народных орнаментах, отражающих мысли и, эмоции их создателей. Создатели: Якшимбетов, Малик (Режиссер); Руднев, А. (Оператор); Карабалин, А. (Оператор); Казахтелефильм (Студия)